STRATEGI PENGELOLAAN SUMBER DAYA MANUSIA DALAM UPAYA MENINGKATKAN DAYA SAING IKM DI KOTA PEKANBARU - Hadiyati, Hadiyati; Fatkhurahman, Fatkhurahman (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
The importance of MSME entrepreneurs moving up a class is a measure of their success in order to increase their contribution to the economy and welfare. However, the current phenomenon is that the competitiveness of MSMEs in moving up a class has experienced poor performance. Human resource management is the main part that needs attention, because the running of a business cannot be separated from the role of human resources, so there needs to be a strategic effort to manage human resources in an effort to increase the competitiveness of MSMEs to move up a class. The output achieved is a strategy on what can be done in managing human resources both in terms of internal and external factors that are owned in order to increase the competitiveness of MSMEs towards moving up a class. The methodology in this study uses a qualitative approach. The informants in this study were MSME business managers and also from policy makers (Pekanbaru city government) and also from academics. Data were collected using questionnaires and interviews and analyzed using SWOT analysis tools. The results of the study indicate that through the identification of internal and external factors, an aggressive strategy can be obtained in managing human resources to increase the competitiveness of MSMEs with strategic policies: 1) Leaders in managing MSME businesses by utilizing information technology; Implementing a positive work culture in facing business globalization; Implementing task specialization in responding to government support in developing human resources.